(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2010)
Summary of results from excavations on three medieval backland properties behind the High Street in Elgin, including a full analysis of timber-lined wells dating from the late 12th/early 13th and 14th centuries. A rare wooden wheel recovered from one of the wells is also illustrated.